1992
DOI: 10.1007/bf00304465
|View full text |Cite
|
Sign up to set email alerts
|

Vascular changes in the spinal cord in N-methyl-d-aspartate-induced excitotoxicity: morphological and permeability studies

Abstract: Our previous studies have demonstrated toxicity in spinal cord neuronal systems of middle-aged rats with continuous intrathecal infusion of N-methyl-D-aspartate (NMDA). The present study was undertaken to determine when during the course of excitotoxicity vascular changes occur. The model used was intrathecal infusion of NMDA in the region of the lumbar enlargement of the spinal cord. Horseradish peroxidase (HRP) was used as a marker of vascular permeability alterations occurring in this model. Pathological ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 23 publications
3
12
0
Order By: Relevance
“…Therefore, it is reasonable to suggest that the NMDA receptor population of neurons may also have a role in MS and EAE. In support of our suggestions, intraventricular, intrathecal, and intrastriatal administration of NMDA to rats has led to the induction of BBB permeability, which is intrinsic to the pathology of MS and EAE (Dietrich et al, 1992;Nag, 1992;Miller et al, 1996). Importantly, the neuronal ␣-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid glutamate receptor has recently been closely linked with neuronal loss and oligodendrocyte depletion during EAE (Pitt et al, 2000;Smith et al, 2000).…”
Section: Discussionsupporting
confidence: 68%
“…Therefore, it is reasonable to suggest that the NMDA receptor population of neurons may also have a role in MS and EAE. In support of our suggestions, intraventricular, intrathecal, and intrastriatal administration of NMDA to rats has led to the induction of BBB permeability, which is intrinsic to the pathology of MS and EAE (Dietrich et al, 1992;Nag, 1992;Miller et al, 1996). Importantly, the neuronal ␣-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid glutamate receptor has recently been closely linked with neuronal loss and oligodendrocyte depletion during EAE (Pitt et al, 2000;Smith et al, 2000).…”
Section: Discussionsupporting
confidence: 68%
“…In addition, confluent deposits of HRP were observed in abluminal caveolae and the adjacent endothelial basement membranes, which did not otherwise contain tracer ( > Figure 3-4b), suggesting that caveolae were depositing HRP in the endothelial basement membrane and the direction of caveolar passage was from the vascular lumen to the subendothelium. This finding was observed in all subsequent studies of experimental hypertension (Nag et al, 1980;Nag, 1984aNag, , 1986Nag and Harik, 1987) and in other models such as spinal cord injury (Beggs and Waggener, 1976), seizures (Hedley-Whyte et al, 1977), bradykinin-induced BBB breakdown (Raymond et al, 1986), and excitotoxic brain damage (Nag, 1992). The active participation of caveolae in transfer of proteins, such as HRP across cerebral endothelium is supported by the absence of such transport in vessels fixed for 45 min before the perfusion of peroxidase .…”
Section: Direction Of Caveolar Passage In Endotheliummentioning
confidence: 73%
“…Multifocal areas of HRP extravasation around cerebral vessels were observed in diverse models, such as hypertension (Nag, 1998); spinal cord injury (Beggs and Waggener, 1976); seizures (Hedley-Whyte et al, 1977;Westergaard, 1980;Nitsch et al, 1986); experimental autoimmune encephalomyelitis (Claudio et al, 1989); excitotoxic brain damage (Nag, 1992); brain trauma (Povlishock et al, 1978), brain tumors ; and BBB breakdown induced by bradykinin (Raymond et al, 1986;Hashizume and Black, 2002), histamine (Dux and Joo, 1982), and leukotriene C4 (Hashizume and Black, 2002), and other models as reviewed previously (Nag, 2003b;Lossinsky and Shivers, 2004). In these studies, HRP was present in all layers of the vessel wall and extended into the gap junctions between astrocytic foot processes and into the adjacent extracellular spaces.…”
Section: Enhanced Transcytosismentioning
confidence: 97%
“…However, this BBB dysfunction is likely secondary to neurotoxicity. Nag (32) found that BBB breakdown in the spinal cord always followed the excitotoxic neuronal lesion after intrathecal NMDA infusion.…”
Section: Discussionmentioning
confidence: 99%